Peat Stabilization by Using Sugarcane Bagasse Ash (SCBA) as a Partial Cement Replacement Materials - Kamaruidzaman, Nazatul Simaa; Abu Talib, Mohd Khaidir; Alias, Nurul Amirah; Adnan, Zainorabidin; Madun, Aziman; Zainal Abidin, Hazreek; Md Dan, Mohd Firdaus (International Journal of Integrated Engineering, 2019)
Malaysia are covered approximately 2.6 million hectare of peat and facing serious geotechnical problems to develop infrastructure on peatland area. This study is to observe the basic geotechnical properties, strength and compressibility behavior of Pontian peat that stabilized by cement (OPC) and sugarcane bagasse ash (SCBA). The whole laboratory test standards and regulation that had been used in this study was adopted from American Society for Testing and Materials (ASTM) and British standards (BS). In order to understand an improvement of peat stabilization, unconfined compressive strength (UCS) and 1D-Oedometer consolidation test were conducted on untreated and stabilized peat. The results show that Pontian peat can be considered as hemic peat with average acidic. It was observed that the treated peat with 5% of SCBA (PCB5) has the highest UCS of 190 kPa and was discovered to be equivalent to PC specimen. There was a noteworthy decrease of void ratio, e for optimum PCB and PC mixtures as compared to untreated peat. The value of Cc and Cα was quite low at small effective stresses, however it improved after beyond preconsolidation pressure, σ’c. Compared to untreated Pontian peat which contributed the ratio of Cα/Cc about 0.056, stabilized peat for PC and PCB5 gave better ratio with 0.0316 and 0.0273 respectively. Results shows that the treated peat Cα/Cc ratios were drop dramatically from untreated peat which is representing the stabilized mixture can efficiently reduce the secondary compression.